Orientasi Kewirausahaan, Kreativitas Program Pemasaran serta Pengaruhnya terhadap Kinerja Pemasaran UMKM: Sebuah agenda Penelitian - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2018)
This concept aims to explain the entrepreneurial orientation, and the creativity of marketing programs on the performance of MSMEs by being mediated by environmental factors. The general proposition in this theory is that marketing performance is a consequence of fit or match or harmony between two or more factors. In the existing studies, it was stated that the entrepreneurial orientation that was used had a significant effect on improving marketing performance. This relationship is not direct, but there are contextual factors that exist in the relationship of entrepreneurial orientation and creativity of marketing programs with marketing performance. The more fit the relationship between entrepreneurial orientation and marketing program creativity with contextual factors, the higher the performance achieved. In a conceptual research in an effort to clarify the constructs of entrepreneurial orientation and the creativity of marketing programs and their relationship to marketing performance, it states that contextual factors are environmental factors. Based on the literature review on the analysis of the factors that influence marketing performance with environmental factors as moderating variables, the theoretical framework that underlies this research concept is developed. In the model or framework, there is a direct influence between entrepreneurial orientation and marketing program creativity on marketing performance. Besides also seen the moderating influence of environmental variables on the relationship. Keywords: Entrepreneurship Orientation, Marketing Program Creativity, Environmental Factors, and MSME Marketing Performance.